Influence of Organizational Culture on Green IT Adoption: Study Literature - Pramuditha Shinta Dewi; Apol Pribadi Subriadi (IPTEK Journal of Proceedings Series, 2019)
Green IT (Information Technology) becomes one of the latest considerations to increase environmental sustainability and reduce the cost of Information Technology operation. However, the successful adoption of Green IT needs Green IT readiness measurement taken for the considerations of organizations leader. Green IT readiness focused on capability and maturity the Green IT effects on the organization. G-Readiness Molla was the integrated framework that usually used for Green IT Readiness. G-Readiness framework had five important dimensions, which were attitude, policy, practice, technology, and governance. Without considering how organization culture affected Green IT adoption. This research purpose was to build the appropriate model for inspecting the effect of organizational culture on the five dimensions of Green IT Readiness, that was Green IT Attitude, Green IT Policy, Green IT Practice, Green IT Technology, and Green IT Governance. Based on our literature review, we proposed a hypothesis: organizational culture was one of the key determinant factors in Green IT Readiness. Thus we updated the G-Readiness Molla framework by adding organizational culture as one of its dimensions